Reconceptualisation of Restorative Justice Approach For Peaceful Dispute Resolution - Soleh, Mukhammad; Santoso, Sigid Budi; Utami, Wiwik; B, Ainu Rofiq; Ayuni, Sinda Eria (LEGAL BRIEF, 2025)
People living in a community have a devoted hope of living in a peaceful environment free from conflict and harmonious social relationships. This dream must be realised via action, determination, and willpower. This project aims to rethink the administration of criminal justice by using Restorative Justice in a straightforward, quick, and cost-free manner. The method used is the normative legal research method because it analyses legal norms that are unclear and inconsistent between one norm and another that regulates restorative justice. The data used is secondary data in the form of primary legal materials, secondary legal materials, and tertiary legal materials, how to obtain legal materials using literature study, analysis of legal materials using qualitative legal analysis using interpretation. Results of the study: The new concept of a simple, fast, and free restorative justice approach in handling minor crimes, namely, carried out by the Head of the Sector Police, the Head of the Resort Police, and the Head of the Regional Police after receiving a peace statement signed by the perpetrator, victim, the perpetrator's family and the victim's family as well as community leaders and investigators who are mediators or facilitators of peace. They were continued by issuing a Letter of Termination of Investigation (SP3).